The Effects of Ergonomic Exercise on Musculoskeletal Disorders among Cleaning Service Officers - Nina Dwi Lestari; Fajar Fauzien; Faudyan Eka Satria (Alta Dharma Publisher, 2021)
Musculoskeletal disorders due to work are a health problem for workers who occupy top positions and impact the quality of life and work productivity. This study aimed to examine the effect of the ergonomic exercise on musculoskeletal disorders due to the cleaning service officers’ workload at Universitas Muhammadiyah Yogyakarta. This study used the Pre-Experiment method with a One-group pre and post-test design. Nineteen cleaning officers were involved in this study. We used the Nordic body map (NBM) questionnaire to assess musculoskeletal disorders. The ergonomics exercise had carried out for 5-10 minutes 3 times a week. This study showed that the mean musculoskeletal disorders before receiving the ergonomic exercise were 45.11. After receiving the intervention, the score of NBM was 39.16. the statistics test found that p-value was 0.000 (p <0.05). It was indicated that ergonomic exercise has a positive effect on musculoskeletal disorders due among cleaning service officers. There is an influence of ergonomic exercise on musculoskeletal complaints due to the cleaning service officers' workload at Universitas Muhammadiyah Yogyakarta. It is necessary to do further research on the effect of ergonomic exercise on musculoskeletal complaints due to work by controlling the factors of age, length of employment, and gender